Co-operative transitions of responsive-polymer coated gold nanoparticles; precision tuning and direct evidence for co-operative aggregation. Issue 34 (8th August 2016) - Won, Sangho; Phillips, Daniel J.; Walker, Marc; Gibson, Matthew I.
Abstract : Responsive polymers and polymer-coated nanoparticles have many potential bio-applications with the crucial parameter being the exact temperature where the transition occurs. Abstract : Responsive polymers and polymer-coated nanoparticles have many potential bio-applications with the crucial parameter being the exact temperature where the transition occurs. Chemical modification of hydrophobic/hydrophilic or ligand binding sites has been widely explored as a tool for controlling this transition, but requires the synthesis of many different components to achieve precise control. This study reports an extensive investigation into the use of blending ( i.e. mixing) as a powerful tool to modulate the transition temperature of poly( N -isopropylacrylamide) (PNIPAM) coated gold nanoparticles. By simply mixing two nanoparticles of different compositions, precise control over the transition temperature can be imposed. This was shown to be flexible to all possible mixing parameters (different polymers on different particles, different polymers on same particles and different sized particles with identical/different polymers). Evidence of the co-operative aggregation of differently sized nanoparticles (with different cloud points) is shown using transmission electron microscopy; particles with higher cloud points aggregate with those with lower cloud points with homo-aggregates not seen, demonstrating the co-operative behaviour. These interactions, and the opportunities for transition tuning will have implications in the rational design of responsive biomaterials.